Efetividade de vídeo educativo para orientação de pais e cuidadores de crianças em uso de cateter uretral intermitente: estudo quase-experimental - Lima, Marília Brito de (2021)
Neurogenic lower urinary tract dysfunction (LUTD) has a considerable impact on the quality of life and daily activities of individuals and their families, requiring follow-up by health professionals. Intermittent Urethral Catheterization (UIC) is the most used therapy in these cases. Through teaching-learning strategies, such as educational videos, nurses promote health promotion actions. The objective was to evaluate the effectiveness of the educational video “Intermittent Urethral Catheterization in children: How to do it?” in the performance of CUI by parents and caregivers of children with neurogenic bladder. This is a quasi experimental study, of the intervention type, carried out from June to October 2021 in a Stomatherapy outpatient clinic of a reference Pediatric Hospital in the state of Ceará. The sample consisted of 30 mothers and/or caregivers who were starting or in continuous use of the CUI, who were evenly distributed into two groups: Intervention Group (IG) and Comparison Group (CG). After accepting and signing the informed consent, the sociodemographic and clinical form, the King’s Health Questionnaire (KHQ) was applied to both groups, as well as the pre-test, which consists of 10 questions about the content of the educational video. GC received routine guidelines from the outpatient clinic and the IG, in addition to the service guidelines, received information through the educational video. After 30 days, the post-test was applied to both groups. Data analyzed and presented as mean and standard deviation. To compare the means between the groups, Student's t and Mann Whitney tests were used. In the associations between the groups, the Fisher's Exact Test was applied. In the analysis of pre- and post-test knowledge between the groups, the Mann-Whitney test was used. Sample composed mostly of women who are married or in a stable union (83%), did not work (86.6%), income of up to R$1,100.00 (67%), domiciled in the countryside (80%), with p of 0.017. After the intervention, the post-test detected a significant difference between the values of the groups, p = 0.013, where the intervention group had higher scores of correct answers with an average of 9.67 of the 10 questions. Regarding the King's Health Questionnaire (KHQ), in the Emotions domain, the IG participants declared level 3, meaning emotional state moderately affected by the child's problem, with a standard deviation of 0.93. In the relationship between anxiety and the child's voiding dysfunction, the CG participants had a mean of 3.2, with a standard deviation of 1.01. The intervention with the educational video aimed at parents and caregivers is effective and contributes to family guidance, in addition to facilitating the understanding, visualization and proper execution of the procedure by parents/caregivers of children with this disorder.